Potential of Therapeutic Bacteriophages in Nosocomial Infection Management - Wu, Nannan; Zhu, Tongyu (Frontiers in Microbiology, 2021)
Antimicrobial resistance (AMR) is a major public health problem usually associated with nosocomial outbreaks and opportunistic infections in hospitalized patients. Conventional treatment and disinfection agents are often insufficient to catch up with the increasing AMR and tolerance of the pathogenic bacteria. This has resulted in a need for alternative approaches and raised new interest in therapeutic bacteriophages (phages). In contrast to the limited clinical options available against AMR bacteria, the extreme abundance and biodiversity of phages in nature enable us to establish an ever-expanding phage library that collectively provides sustained broad-spectrum and poly-microbial coverage. Given the specificity of phage-host interactions, phage susceptibility testing can serve as a rapid and cost-effective method for bacterial subtyping. The library can also provide a database for routine monitoring of nosocomial infections as a prelude to preparing ready-to-use phages for patient treatment and environmental sterilization. Despite the remaining obstacles for clinical application of phages, the establishment of phage libraries, pre-stocked phage vials prepared to good manufacturing practice (GMP) standards, and pre-optimized phage screening technology will facilitate efforts to make phages available as modern medicine. This may provide the breakthrough needed to demonstrate the great potential in nosocomial infection management.